The Perception of Farmers on Soil Erosion and Conservation Measures in the Surrounding Areas of Lake Ziway, Central Rift Valley of Ethiopia - Daniel Jaleta Negasa (Applied and Environmental Soil Science)
The level of sediment deposited in the Lake Ziway is increasing through time as a result of soil erosion, and eventually the depth of the lake has decreased. Therefore, the objective of the study was to assess farmers’ perception of soil erosion and the conservation measures to the surrounding areas of Lake Ziway in the central Rift Valley of Ethiopia. The survey was made using purposive sampling techniques. The survey has considered the 14 Kebeles from the 3 districts adjacent to the lake. From each Kebele, 10 respondents were selected randomly. Totally, 140 respondents were selected from the community. The descriptive statistic was used to compare the dependent variables. The majority of respondents (92.2%) have observed the presence of soil erosion in the study area. The hillsides and slope areas are the major sources of soil erosion, according to 80% of the respondents. The respondents that have identified the most and least susceptible soils to erosion by their textural classes are sand soil (Biyyo Chirecha) (57.1%) and soft clay soil (Biyyo Bole) (1.4%), respectively. The soil erosion is increasing in their cultivated land and surrounding areas. The study has found that most of the respondents (86.5%) are participating in soil and water conservation activities. Leucaena leucocephala, Faidherbia albida, Azadirachta indica, and Schinus molle are the dominant tree species planted in the study area for soil and water conservation purposes. In conclusion, there is heavy soil loss due to erosion on cultivated land from the upland which directly deposited to Lake Ziway as sediment which decreases the lake depth. The study recommends that appropriate soil and water conservation measures and land management should be implemented on erosion prone areas in the Lake Ziway watershed with full participation of all stakeholders including the local farmers.